Progress and challenges in forecast verification. (22nd May 2013) - Ebert, E.; Wilson, L.; Weigel, A.; Mittermaier, M.; Nurmi, P.; Gill, P.; Göber, M.; Joslyn, S.; Brown, B.; Fowler, T.; Watkins, A.
ABSTRACT Verification scientists and practitioners came together at the 5th International Verification Methods Workshop in Melbourne, Australia, in December 2011 to discuss methods for evaluating forecasts within a wide variety of applications. Progress has been made in many areas including improved verification reporting, wider use of diagnostic verification, development of new scores and techniques for difficult problems, and evaluation of forecasts for applications using meteorological information. There are many interesting challenges, particularly the improvement of methods to verify high resolution ensemble forecasts, seamless predictions spanning multiple spatial and temporal scales, and multivariate forecasts. Greater efforts are needed to make best use of new observations, forge greater links between data assimilation and verification, and develop better and more intuitive forecast verification products for end‐users. Copyright © 2013 Royal Meteorological Society